Redox mechanisms of environmental toxicants on male reproductive function - Hussain, Tarique; Metwally, Elsayed; Murtaza, Ghulam; Kalhoro, Dildar Hussain; Chughtai, Muhammad Ismail; Tan, Bie; Omur, Ali Dogan; Tunio, Shakeel Ahmed; Akbar, Muhammad Shahzad; Kalhoro, Muhammad Saleem (Frontiers in Cell and Developmental Biology, 2024)
Humans and wildlife, including domesticated animals, are exposed to a myriad of environmental contaminants that are derived from various human activities, including agricultural, household, cosmetic, pharmaceutical, and industrial products. Excessive exposure to pesticides, heavy metals and phthalates consequently causes the overproduction of reactive oxygen species. The equilibrium between reactive oxygen species and the antioxidant system is preserved to maintain cellular redox homeostasis. Mitochondria display a key role in cellular function and cell survival. The mitochondria are vulnerable to damage that may be provoked by environmental exposures. Once the mitochondrial metabolism is damaged that interfere in energy metabolism and eventually causes the overproduction of free radicals. Further, it also perceives inflammation signals to generate inflammatory response which is involved in pathophysiological mechanisms. A depleted antioxidant system provokes oxidative stress that triggers inflammation, and regulates epigenetic function and apoptotic events. Apart from that, these chemicals influence steroidogenesis, deteriorate sperm quality and damage to male reproductive organs. It is strongly believed that redox signaling molecules are the key regulators that mediate reproductive toxicity. This review article aims to spotlight the redox toxicology of environmental chemicals on male reproduction function and its fertility prognosis. Furthermore, we will shed light on the influence of redox signaling and metabolism in modulating the response of environmental toxins on reproductive function. Additionally, we will emphasize the supporting evidence from diverse cellular and animal studies.